BAKAT DAN PENGARUHNYA TERHADAP PENCAPAIAN PRESTASI BELAJAR SISWA - Alang, M. Sattu (Jurusan Bimbingan dan Penyuluhan Islam, 2023)
Talent is a natural ability of a person that still needs to be trained and developed in order to achieve its full potential. Meanwhile, ability is the power to perform an action as a result of innate qualities and practice. Talent also influences an individual's learning activities. If the subjects or materials being studied by a student are not aligned with their talent, they will experience learning difficulties, which can impact both their academic performance and the teacher's ability to address it. Each individual possesses unique talents. Some may have artistic talents, others may excel in statistics, sports, and various other fields. The rights and responsibilities of students or learners include receiving educational services tailored to their talents, interests, and abilities, while also being obliged to uphold educational norms to ensure the continuity and success of the learning process. Therefore, a student's learning achievement is defined as the qualitative and quantitative measure of what they have achieved through the learning and teaching process. Differences in talent will significantly influence an individual's learning style, which in turn affects their success in achieving academic accomplishments.